The Threshold Requirements For Presidential Nomination On The Constitutional Perspective - Sabrina, Dian Fitri; Sukardi (Media Iuris, 2024)
AbstractThe presidential nomination model through the threshold is a provision regulated in the election law. The practice of presidential elections in Indonesia is often a difficult moment for both political parties and citizens. Several decisions of the Constitutional Court related to the review of Law Number 7 of 2017 concerning Elections, particularly regarding the threshold for declaring Article 222 of the Election Law not contradicting the constitution, meaning that Article 222 of the Election Law is considered to have complied with Article 6A paragraph (2) of the Constitution, but from the results research on article 222 of the Election Law still does not reflect the meaning contained in article 6A paragraph 2 of the Constitution. This research aims to build a presidential nomination model in the 2024 general election in Indonesia. This research is a doctrinal research using a case approach and a legal approach. This study was conducted by looking at the practice of the electoral threshold model for the 2004, 2009, 2014 and 2019 periods as well as the provisions stipulated in the Election Law and the constitution. The results of the study indicate that it is necessary to form an ideal presidential candidacy model, namely using the maximum threshold as a requirement, in order to produce qualified presidential candidates who become leaders who are responsible, have integrity and are the hope of all Indonesian citizens.Keywords: Threshold Requirements; Presidential Nomination; Constitutional Perspective.